Assessment of health promoting life styles among the under graduate students of Sri Venkateswara Institute of Medical Sciences (SVIMS) University, Tirupati, Andhra Pradesh - Deekala, Ravi Sankar; Sujith Kumar Dondapati, Srinivasa; Damu Ade, Anju; Yamasani, Bhavani; Kandra, Naga Vishnu; Mahammad Shareef, Suleman (Public Health Review: International Journal of Public Health Research, 2017)
Background: Health promoting behaviours, including self-initiated actions, behaviours, and health perceptions may have an impact on individual happiness and well-being. Objectives: To study health promoting life style among the first year under graduate students of Sri Venkateswara Institute of Medical Sciences University and compare the health promoting life style profiles between the first year under graduate students of different courses of the University. Methods: A Self-administered Questionnaire containing Health Promoting Life Style Profile - II questionnaire developed by Walker etal. was distributed to the students and were asked to answer all the questions and return the same. Results: A total of 354 students participated in the study. Of these students 42%, 28%, 16% and 14% were pursuing MBBS, Bachelor of Physiotherapy, BSc Nursing and BSc Paramedical courses respectively. Students had highest score in Interpersonal relations (2.98 ± 0.45), Spiritual growth (2.91 ± 0.45) and Stress management (2.63 ± 0.43). Lowest scores in Physical activity (2.08 ± 0.6), Health Responsibility (2.18 ± 0.5) and Nutrition (2.4 ± 0.44). Conclusion: There was no significant difference between specialities in terms of HPLP scale scores and all subscale scores.